Short Communication: Tetrazolium test for evaluating viability of Capsicum annum seeds - ADITYA KUSUMAWARDANA; BAMBANG PUJIASMANTO; PARDONO PARDONO (Nusantara Bioscience, 2018)
Kusumawardana A, Pujiasmanto B, Pardono. 2018. Tetrazolium test for evaluating viability of Capsicum annum seeds. Nusantara Bioscience 10: 142-145. Seed quality is important in seeds production. This research was conducted to obtain information of topographical tetrazolium staining pattern of pepper (Capsicum annum) seeds. Tetrazolium test was conducted to determine the seed viability and plant growth vigor. Laboratory test for standard germination and field performances were performed on four lots (A, B, C, D) of pepper seeds. The viability categories pattern were determined by Root Mean Square (RMS), regression, and correlation analyses. Nine topographical patterns were recognized. The laboratory test results and field performances were compared with the topographical pattern. Combination of patterns 1,2 (embryonic axis and cotyledon completely stained) selected as viable category as it gave the least RMS value, the highest determination (R²) and correlation (r) coefficient with standard germination (RMS = 4, 06; R² = 0,761; r = 0,872). Combination of patterns 1,2 also gave the highest determination (R²) and correlation (r) coefficient with field stand (R² = 0,921; r = 0,959). The combination of patterns 1,2 is recommended for estimating plant growth performance in the field.